Foragent export agent - Busu, Ruhana; Mohamed, Zainal Abidin; Tan, H. T. (Universiti Putra Malaysia Press, 2008)
This case is about the process a forwarding agent had to undergo to document three major processes: importing, exporting, and billing. These major processes were recorded and tabulated to facilitate (1) easy understanding of the processes and (2) reengineering of processes. The case is appropriate for small and medium enterprises to follow in documenting processes and reengineering them by merging, collapsing and removing, and rearranging. The case also suggests ways to insert technologies and innovations at appropriate steps of the processes.